Pengembangan LKPD Berbasis Materi Prasyarat Terstruktur pada Materi Persamaan Garis Lurus untuk Kelas VIII SMP/MTs: Development of LKPD Based on Structured Prerequisite Material on Straight Line Equation Material for VIII SMP/MTs Class - Sariyani SN; Jefri Marzal; Syaiful Syaiful (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2020)
Mastery of the prerequisite material is essential to help students overcome mathematics learning difficulties; however, the prerequisite material needs to be managed effectively to achieve learning objectives. Student Worksheet (LKPD) is a learning tool that can be used to achieve learning objectives. This research is development research to produce a student worksheet that is valid, practical, and effective. LKPD development is carried out using the ADDIE model. The valid value is obtained from the results of content validation by the validator. The practical value is obtained from the test subject's response, and the effectiveness value is obtained based on the assessment of students during the actual trial. The development results show that the average percentage score of the validation results of material experts and media experts reaches 72%, which indicates that LKPD is valid. The practicality assessment was obtained from the percentage of student and teacher responses to the questionnaire given; the average is 99%. The trial results show that the students' responses are very valid. Student learning outcomes showed that 76% of students were able to reach the minimum requirement achievement, meaning that the LKPD effectively improved student learning outcomes. Mathematical LKPD based on structured prerequisite material fulfills the valid, practical, and effective criteria for learning straight line equation material.